Religious and Cultural Dimensions of the Rebo Wekasan Tradition in Gresik, Indonesia: An Ethnographic Study - Maghfiroh, Lailatul; Yatmin, Yatmin; Afandi, Zainal; Yudha, Gesit (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background: Indonesia has a rich cultural tradition that reflects the religious and social values of the local community. One of these traditions is Rebo Wekasan which is held on the last Wednesday of the month of Shafar. This tradition is still preserved by the people of Sacred Village, Manyar District, Gresik Regency, even though the times continue to change. Aims: This research aims to uncover the historical origins, symbolic meaning, and procession of the implementation of the Rebo Wekasan Tradition in the Holy Village, as well as understand the role of these traditions in strengthening the collective identity and religious expression of the community. Methods: The research uses a qualitative approach with ethnographic methods. Data collection was carried out through in-depth interviews, direct observation of traditional activities, and documentation. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. Result: The results of the study show that the Rebo Wekasan Tradition has a close relationship with the history of the spread of Islam by Sheikh Jamaluddin Malik. This tradition contains the values of gratitude, spiritual protection, friendship, and almsgiving. The processions carried out included Qur'an sermons, tumpeng carnivals, joint prayers, istighosah, and people's markets. This tradition not only survives but also adapts to the social dynamics of modern society. Conclusion: The Rebo Wekasan tradition remains the cultural and spiritual binder of the people of the Holy Village. It becomes a meaningful space for social interaction and the preservation of local wisdom values across generations. Its sustainability proves that cultural traditions can survive and adapt in the midst of changing times.